Itch as a critical factor in impaired health-related quality of life in patients with plaque psoriasis achieving clear or almost-clear skin: Analysis of the single-arm, open-label, multicenter, prospective ProLOGUE studyCapsule Summary - Takuya Miyagi, MD; Yasumasa Kanai, PhD; Kenta Murotani, PhD; Yukari Okubo, MD, PhD; Masaru Honma, MD, PhD; Satomi Kobayashi, MD, PhD; Mariko Seishima, MD, PhD; Yoko Mizutani, MD, PhD; Hiroki Kitabayashi, MSc, MPH; Shinichi Imafuku, MD, PhD (Elsevier, 2022)
Background: Patients with psoriasis report impaired health-related quality of life (HRQoL; Dermatology Life Quality Index score ≥ 2) even after achieving clear or almost-clear skin with biologic treatment. Objective: To assess the effectiveness of brodalumab in HRQoL improvement and the factors associated with incomplete HRQoL improvement in Japanese patients with psoriasis. Methods: As a part of the single-arm, open-label, multicenter, prospective ProLOGUE study (Japan Registry of Clinical Trials identifier: jRCTs031180037), patients were treated with 210 mg of subcutaneous brodalumab in daily clinical practice until week 48. The absolute Psoriasis Area and Severity Index scores and patient-reported outcomes were assessed at baseline and weeks 12 and 48. Results: Seventy-three patients (male, 82.2%; median age, 54.0 years) were enrolled. The Dermatology Life Quality Index and European Quality of Life 5-Dimension 5-Level Utility Index scores significantly improved from baseline to weeks 12 and 48. At week 48, all 13 patients with a Dermatology Life Quality Index score of ≥2 and an absolute Psoriasis Area and Severity Index score of 0 to ≤2 reported itching. Limitations: Unclear generalizability of the results to other biologics. Conclusion: Treatment with brodalumab improved HRQoL in patients with psoriasis. Itching may contribute to incomplete HRQoL improvement in patients who have achieved clear or almost-clear skin.